PDevelopments in mathematics and computers in sport in Australia - Hammond, J.; de Mestre, N. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Mathematics und computers in sport is seen as contribution to sports scicnce both directly and indirectly through other science disciplines. This paper describes the history of the MathSport group in Australia and New Zealand through papers and presentations at biennial conferences. The MathSport group began its input into the body of knowledge in sports science in the early 1990s and has continued to contribute in both research and scholarship up to the present day. The variety of contributions in terms of different sports, theoretical frameworks and modes of analysis has increased in volume since those early days.